Nilai-Nilai Kearifan Lokal dalam Pengelolaan Sumber Daya Air di Telaga Omang dan Ngloro Kecamatan Saptosari, Gunung Kidul Yogyakarta - Mr. Sulastriyono (Fakultas Hukum Universitas Gadjah Mada, 2009)
Lake is located in every village in Gunung Kidul regency whether big ones or little ones. This is for example Omang and Ngloro Lake in Saptosari district, which are chose as location for this research. Those Lakers are used for several activities. This research aims to describe local wisdom owned by the community on how they manage the resources. Furthermore, this research describes obstacle in resources management and find Solutions for it. Data collection is obtained from library. Primary data management and find are gained from field study with interview and observation non participatory methods. Both data were combined and then analyzed qualitatively. The result of this research shows that; reality of the local wisdom in Omang pond is different with the local wisdom in Ngloro pond. There are technical, structural and cultural obstacles to manage the water pond resources. Too many rubbish from pond user according to the local population growth caused the pond dirty and water seems green. The local community joint with governmental and nongovernmental institutions to solve the problems.